Optimasi Jalur Tercepat dengan Menggunakan Modifikasi Algoritma Bellman Ford (Studi Kasus Lintas Antar Kecamatan Kota Malang) - Agustian Aji (Fakultas Teknik, Universitas Brawijaya, 2015)
Abstract— In the study application of the calculation method of modification of Bellman Ford is aiming to find the fastest path between districts in the city of Malang . Bellman method calculates all the paths of the place of origin of the place of destination with the help of GPS . Testing Bellman Ford modify their direct and produce Comparing these same route as much as 2 % of a modified Bellman Ford is best after the modified . Bellman was also good enough to be used as the calculation of the level of road width , road conditions , vehicle ramp and volume. The conclusion that can be drawn is the use of application design Bellman appropriate or suitable partner in the search for the fastest track in the city of Malang.Keywords : Line fastest , Bellman Ford , GPS